Association Between Dietary Patterns and Dyslipidemia in Korean Women - Lee, Jeonghee; Hoang, Tung; Lee, Seohyun; Kim, Jeongseon (Frontiers in Nutrition, 2022)
Background: The prevalence of dyslipidemia among Korean women differs significantly according to menopausal status. This study aimed to identify major dietary patterns among Korean women and examine their associations with the prevalence of dyslipidemia and its components. Methods: This study recruited 6,166 women from the Cancer Screenee Cohort 2007-2019 from the National Cancer Center of Korea. Dietary patterns were identified using factor analysis. Multivariable logistic regression was performed to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for the associations between dietary patterns and the prevalence of dyslipidemia and its components, including hypercholesterolemia, hypertriglyceridemia, hypo-high-density lipoprotein (HDL) cholesterol, and hyper-low-density lipoprotein (LDL) cholesterol. Stratification analyses were performed for the premenopausal and postmenopausal subgroups. Results: The factor analysis identified three main dietary patterns, including traditional, western, and prudent dietary patterns. Compared with those with the lowest pattern scores, those with the highest pattern scores of the traditional (OR=1.32, 95% CI=1.05-1.67) and western (OR=1.40, 95% CI=1.11-1.78) diets had a higher prevalence of hyper-LDL cholesterol. When accounting for menopausal status in the analysis, traditional (OR=1.44, 95% CI=1.10-1.89) and western (OR=1.43, 95% CI=1.09-1.88) diets were still associated with hyper-LDL cholesterol in postmenopausal women. Additionally, consumption of a traditional diet was associated with a decreased prevalence of hypertriglyceridemia (OR=0.73, 95% CI=0.54-0.99), and consumption of a western diet was associated with an increased prevalence of hypercholesterolemia (OR=1.41, 95% CI=1.11-1.79) but a reduced prevalence of hypo-HDL cholesterol (OR=0.60, 95% CI=0.36-0.99). However, the prudent dietary pattern was not significantly associated with dyslipidemia and its components in the group of all women or the subgroups according to menopausal status. Conclusion: There were significant associations between the traditional and western dietary patterns and hyper-LDL cholesterol in the entire group and postmenopausal subgroup of women. In the perspective of energy restriction, our findings recommend women not to eat either traditional or western diets excessively or too frequently. Menopause may induce the effect of both the traditional diet on triglyceride reduction and the western diet on increasing total cholesterol.